Endogeneity and Nonlinearity in the Environmental Kuznets Curve: A Control Function Approach - (:unkn) unknown (SAVEZ EKONOMISTA VOJVODINE, 2021)
This study investigates the existence and shape of an environmental Kuznets curve (EKC) across 16 developed countries and 58 developing countries during the period 1995-2010. The basic model of the EKC is a polynomial equation of real GDP per capita. The EKC model estimated for CO2 emission per capita was extended by using control variables, such as trade, urban population, fossil fuel consumption, and service sector. Based on the nonparametric test of poolability of Badi H. Baltagi, Javier Hidalgo, and Qi Li (1996), the relationship was found to have structural stability. A nonparametric pooled regression model was constructed, which allowed functional form flexibility and considered the endogeneity problem often emphasized in the EKC literature. The estimation results show the nonexistence of an EKC for both groups. The study also indicates the existence of nonlinearity and heterogeneity in the relationships between CO2 emission and the control variables across both groups.
Keywords: Environmental Kuznets curve; CO2 emissions; Nonparametric models; Endogeneity; Control function approach; CARBON-DIOXIDE EMISSIONS; CO2 EMISSIONS; ECONOMIC-GROWTH; ENERGY-CONSUMPTION; NONPARAMETRIC REGRESSION; TRADE; HETEROGENEITY; URBANIZATION; HOMOGENEITY; HYPOTHESIS